Constrains Faced by the Farmers in Shrimp Culture: An Empirical Investigation from Selected Areas of Bagerhat District - Hira, Bibekananda; Rahman, Md Asifur; Mazumder, Mohummed Shofi Ullah; Ali, Md Sekender; Masum, Abdullah Al (Journal of the Bangladesh Agricultural University, 2025)
Shrimp cultivation is having a significant impact on the economy and socio-economic status of the coastal regions in Bangladesh. Here, we investigated the constrains faced by the farmers towards shrimp culture, and to identify the influential factor affecting farmer constrains in shrimp culture. Data were collected from nine villages of Char Baniari union under Chitalmari sub-district of Bagerhat district purposefully. Yamane's (1967) technique was used to randomly choose 90 shrimp farmers for personal interviews. ‘Constraints faced by the farmers in shrimp culture’ was the focus variable of the study which was measured by using a 4-point rating scale. A score of 3, 2, 1, and 0 was assigned to the categories of "high," "medium," "low," and "not at all" in the responses. The data was analyzed using a combination of descriptive and inferential statistics, including multiple linear regression and stepwise regression models. The majority of farmers (68.90%) was found with facing a high level of constrains in shrimp culture. The results from multiple linear regression identified that age, education, and contact with extension media were noticed as the significant influential variables explaining 53.5% variation. Experienced farmers should be encouraged to participate in shrimp culture so that their experience can be utilized properly. The Ministry of Education and local level non-government organizations (NGOs) should collaborate to implement adult education programme. Additionally, extension workers must ensure that all farmers can access the extension service. J Bangladesh Agril Univ 23(1): 50–58, 2025